Embracing Wobble: Exploring Novice Teachers' Efforts to Enact Dialogic Literacy Instruction. Issue 3 (24th April 2019) - Stewart, Trevor Thomas; Coombs, Dawan; Fecho, Bob; Hawley, Todd
Abstract: Contemporary school contexts present challenges for novice teachers seeking to support students' literacy development by bringing content into dialogue with students' lives. These challenges, framed as wobble moments, often contribute to high rates of teacher attrition. However, dialogue with peers, colleagues, and mentors can help teachers learn from the tensions they encounter as they enact dialogic literacy instruction. The authors share the struggles of novice teachers working to enact dialogical practices and describe how an oral inquiry process framework helped them negotiate these challenges. Working from a Bakhtinian stance, the authors present three wobble moments that were connected to school structures, personal and professional identities, and conformity to demonstrate how the oral inquiry process helped the participants learn from the difficulties they faced. Findings suggest that the oral inquiry process framework can help teachers navigate difficulty through dialogue and enact pathways that empower them. Recommendations for implementing this framework are also included.